In vitro antibacterial and time kill evaluation of mononuclear phosphanegold(I) dithiocarbamates - Chen, Bao-Jing; Nazzatush Shimar Jamaludin,; Khoo, Chai-Hoon; See, Tian-Hong; Sim, Jiun-Horng; Cheah, Yoke-Kqueen; Siti Nadiah Abdul Halim,; Seng, Hoi-Ling *; Tiekink, Edward R. T. * (Elsevier, 2016)
Four compounds, R3PAu[S2CN(CH2CH2OH)2], R=Ph (1) and cyclohexyl (2), and Et3PAuS2CNRꞌ2, Rꞌ=Rꞌ=Et (3) and Rꞌ2 = (CH2)4 (4), have been evaluated for antibacterial activity against a panel of 24 Gram positive (8) and Gram negative (16) bacteria. Based on minimuminhibitory concentration (MIC) scores, compounds 1 and 2 were shown tobe specifically potent against Grampositive bacteriawhereas compounds 3 and, to a lesser extent, 4 exhibited broad range activity. All four compounds were active against methicillin resistant Staphylococcus aureus (MRSA). Time kill assays revealed the compounds to exhibit both time- and concentration-dependent pharmacokinetics against susceptible bacteria. Each compound was bactericidal against one or more bacteria with 3 being especially potent after 8 h exposure; compounds 1 and 3were bactericidal againstMRSA. Compound 3 was the most effective bactericide across the series especially toward B. subtilis, S. saprophyticus, A. hydrophila, P. vulgaris, and V. parahaemolyticus. This study demonstrates the potential of this class of compounds as antibacterial agents, either broad range or against specific bacteria.